EMPOWERMENT OF WOMEN FARMERS INDIGENOUS PEOPLES OF KASEPUHAN BANTEN KIDUL - Mirajiani Mirajiani; Siti Widiati; Gugun Gunawan (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2022)
The Kasepuhan Indigenous Peoples of Banten Kidul are one of the Indigenous communities in Banten Province, Lebak Regency, which are spread over several Traditional Villages including Kasepuhan Ciptagelar, Cisungsang, Cisitu, Cicarucub, Citorek, and Cibedug. Indigenous people of Banten Kidul still apply beliefs according to local wisdom- based traditional customs in their lives. The research aims to explore the role of Kasepuhan women farmers within the framework of Kasepuhan customs and examine how to empower women farmers in Kasepuhan The research uses descriptive techniques and a qualitative approach. The research location is in Kasepuhan Banten Cicarucub which is one of the Indigenous People of Kasepuhan Banten Kidul in Lebak Regency, Banten Province. The importance of the role of women in the Kasepuhan traditional framework shows the significance of empowering women on the basis of existing rules and culture which is local wisdom that must be preserved for generations. The role of women in household and family domestic activities makes women play a very important role in independence to meet family food needs, both in quantity and quality of food consumed by the family. Empowerment of Women Farmers in Kasepuhan Cicaracub should not violate customary rules that are maintained for generations, can increase knowledge and skills capacity in domestic affairs and household productive activities, be able to generate participation and initiatives to increase women's independence, can improve the standard of living of the Kasepuhan indigenous people in harmony with efforts to maintain traditional uniqueness, local wisdom, and preserve the environment and cultural customs that have been well-maintained so far